If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19(62x + 4) = -19(-4x + -236) Reorder the terms: 19(4 + 62x) = -19(-4x + -236) (4 * 19 + 62x * 19) = -19(-4x + -236) (76 + 1178x) = -19(-4x + -236) Reorder the terms: 76 + 1178x = -19(-236 + -4x) 76 + 1178x = (-236 * -19 + -4x * -19) 76 + 1178x = (4484 + 76x) Solving 76 + 1178x = 4484 + 76x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-76x' to each side of the equation. 76 + 1178x + -76x = 4484 + 76x + -76x Combine like terms: 1178x + -76x = 1102x 76 + 1102x = 4484 + 76x + -76x Combine like terms: 76x + -76x = 0 76 + 1102x = 4484 + 0 76 + 1102x = 4484 Add '-76' to each side of the equation. 76 + -76 + 1102x = 4484 + -76 Combine like terms: 76 + -76 = 0 0 + 1102x = 4484 + -76 1102x = 4484 + -76 Combine like terms: 4484 + -76 = 4408 1102x = 4408 Divide each side by '1102'. x = 4 Simplifying x = 4
| 4y^2-256=0 | | 24=0.5b*6 | | m^2-10=279 | | 2/7(x-9)=4 | | 7e^2x=285 | | -35=-5x+5(4x+11) | | 2lnx+1=7 | | 19(26x+4)=-19(-4x-236) | | 4(a+h)-7/(a+h)-2 | | -35=15x+5(4x+11) | | 14-w=21-3w | | 6x+6.91=3x+10 | | 7x-4+5x+8+90=180 | | p+10.1=10.45 | | (4x-7)/(x-2) | | 50x+.50= | | -158=-7x+4(4x-17) | | 2x+3(-3x+18)=103 | | b^2+2b-30=5 | | p=18-4/3q | | x^6-8x^4+4x^3+3x^2+4x+12=0 | | 7x-2(5x+14)=-49 | | p(8p+7)(8p-7)= | | px(8p+7)x(8p-7)= | | 4b^2+24b+11=0 | | 5x^2-26x+24= | | -114=-6x+5(-x-3) | | 6w=70-8w | | Y=-3(-9)-29 | | 191=-4x+5(5x+13) | | 29.95+.13x=.39 | | 5x-5(3x-12)=-50 |